From research on the topography and systematics of Roman defensive fortifications in the area of present-day Bulgaria - Biernacka-Lubańska, Małgorzata (Balcanica Posnaniensia. Acta et studia, 1990)
The article concerns the topography and systematics of Roman defensive fortifications in the area of present-day Bulgaria. The research problem includes the classification and function of various types of fortifications in Lower Moesia and northern Thrace. The aim of the work is to organize knowledge about the defensive system and its significance within the structure of the Roman Empire. The author applies archaeological and topographical analysis. The most important results indicate the existence of two main types of fortifications: frontier and internal, among which the Danubian limes fortifications were of key importance. These included various forms such as castra, castella, and burgi. The fortifications were strategically located along the Danube and connected with a network of roads and river ports, which enabled efficient communication and defense of the borders. The conclusion emphasizes the complexity and high level of organization of the Roman defensive system.